Training of professionals on child rights - Herczog, Mária (European Integration Studies, 2023)
It is universally recognized that children have rights that are inalienable and indivisible. All children are entitled to be aware of and excercise their rights The exposure, experience and education that children receive in their formative years determines their development and well-being. The United Nations Convention on Rights of the Child (UNCRC) set the guiding principles and its implementation, including awareness raising, education about child rights for all, including children themselves, parents, professionals and the public. The ultimate aim of the education, training on child rights for professionals is to sensitize, inform them and ensure that they are working with children in line with the principles and requirements of the UNCRC and other relevant child rights related treaties and documents. There has been so far limited efforts made to train all professionals in contact with children to learn about child rights and skills on how to implement them, involving children, raising awareness of their rights and support the use of them in their everyday life. Children play a central role in shaping the present and future, with adults offering the support required, for children’s well-being and to reach their full potential, so that in collaboration, children and adults can strengthen and transform our world. To achieve this vision, children, parents, professional and the public needs to be aware of child rights and implement them properly. The article provides an overview of the current situation worldwide and describes a number of programs, trainings provided as promising practices.